2015
DOI: 10.1002/micr.22480
|View full text |Cite
|
Sign up to set email alerts
|

The potential roles for adipose tissue in peripheral nerve regeneration

Abstract: Introduction This review summarizes current understanding about the role of adipose-derived tissues in peripheral nerve regeneration and discusses potential advances that would translate this approach into the clinic. Methods We searched PubMed for in vivo, experimental studies on the regenerative effects of adipose-derived tissues on peripheral nerve injuries. We summarized the methods and results for the 42 experiments. Results Adipose-derived tissues enhanced peripheral nerve regeneration in 86% of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 80 publications
(134 reference statements)
2
15
0
Order By: Relevance
“…33 Therefore, we chose rASCs to accelerate peripheral nerve regeneration because it has been shown that ASCs enhance peripheral nerve regeneration in 86% of experiments. 34 Our results are also in line with those of Song et al 35 These researchers reported that ASCs significantly improved the erectile response to cavernous nerve stimulation and increased endogenous phosphor-endothelial nitric oxide synthase phosphorylation and angiogenic factors compared with controls (nerve crush and phosphate buffered saline). 35 For future studies, we will evaluate the effect of CR-only as a comparison group.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…33 Therefore, we chose rASCs to accelerate peripheral nerve regeneration because it has been shown that ASCs enhance peripheral nerve regeneration in 86% of experiments. 34 Our results are also in line with those of Song et al 35 These researchers reported that ASCs significantly improved the erectile response to cavernous nerve stimulation and increased endogenous phosphor-endothelial nitric oxide synthase phosphorylation and angiogenic factors compared with controls (nerve crush and phosphate buffered saline). 35 For future studies, we will evaluate the effect of CR-only as a comparison group.…”
Section: Discussionsupporting
confidence: 91%
“…However, samples of amniotic membrane must be collected immediately after caesarean surgery . Therefore, we chose rASCs to accelerate peripheral nerve regeneration because it has been shown that ASCs enhance peripheral nerve regeneration in 86% of experiments …”
Section: Discussionmentioning
confidence: 99%
“…In particular, differentiated ASCs could be a clinically translatable route toward new methods to enhance peripheral nerve repair (Kappos et al., ). Thus, we selected epineural rASC injection with the idea to boost peripheral nerve regeneration as it has be shown that ASCs enhance peripheral nerve regeneration in 86% of the experiments (Walocko, Khouri, Urbanchek, Levi, & Cederna, ). However, it has been suggested that it is possible for peripheral nerve fibers to spontaneously regenerate when continuity of the nerve is maintained during injury (Walocko et al., ), such as in our current study.…”
Section: Discussionmentioning
confidence: 99%
“…However, they can be effectively differentiated along ectodermal lines, with SC‐like ADSCs, first described in 2007 by Kingham and colleagues . Numerous studies have focused on neuroregenerative effects of adipose tissue using purified, cultured, differentiated, or dedifferentiated adipose‐derived tissues . ADSCs have also been extensively investigated for use in peripheral nerve regeneration, with promising results.…”
Section: Adipose‐derived Stem Cellsmentioning
confidence: 99%
“…38 Numerous studies have focused on neuroregenerative effects of adipose tissue using purified, cultured, differentiated, or dedifferentiated adipose-derived tissues. [59][60][61] ADSCs have also been extensively investigated for use in peripheral nerve regeneration, with promising results. They produce mRNA for the growth factors BDNF, glial-growth-like factor (GGF), neurogulin-1 (NRG-1), vascular endothelial growth factor (VEGF), hepatocyte growth factor (HGF), and insulin-like growth factor (IGF) on par or greater than SCs in culture.…”
Section: Adipose-derived Stem Cellsmentioning
confidence: 99%